Economic Transformation Of Jember Post-Covid-19: Progress In Micro, Small, Medium Enterprises (MSMES) - Ahsani, Nasirudin Al; Andriani, Nita; Islami Rahayu, Nurul Widyawati (Majalah Ilmiah DIAN ILMU, 2024)
Covid-19 pandemic has had a significant impact on various aspects of life in Jember Regency. Economic growth contracted deeply, with a recorded decrease of -2.98 percent in 2020. The effects of this economic contraction also influenced the unemployment rate, which increased by 19 thousand people according to data from the Central Statistics Agency (BPS). Additionally, the number of people living in poverty also increased, adding up to 21 thousand individuals. Income inequality between the rich and poor, measured by the Gini Index, indicates a moderate level of inequality, suggesting significant disparities. Furthermore, the Human Development Index (HDI) in Jember Regency is still lower than the average in East Java, indicating an urgent need for improving the quality of life for residents. The objective of this research is to analyze the changes and progress in the MSME sector. The research was conducted through library research. The results of this study indicate: 1) healthy competition through the organization of the Excellent Expo MSME 2021 and Geber MSME Jember Expo 2021, 2) investment by the government through collaboration with OK OCE, 3) education and training conducted by the regency government through the Cooperative and Microenterprise Agency (Diskopum), 4) innovation, the regency government innovates by providing facilities for managing NIB, PIRT, Halal, HAKI, and digital-based payments, 5) industrial dynamics, the number of active MSMEs in Jember has significantly increased from before, reaching more than 25,000 business units in 2024, an increase from the previous year.